2x-4y+10=0

Simple and best practice solution for 2x-4y+10=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2x-4y+10=0 equation:


Simplifying
2x + -4y + 10 = 0

Reorder the terms:
10 + 2x + -4y = 0

Solving
10 + 2x + -4y = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-10' to each side of the equation.
10 + 2x + -10 + -4y = 0 + -10

Reorder the terms:
10 + -10 + 2x + -4y = 0 + -10

Combine like terms: 10 + -10 = 0
0 + 2x + -4y = 0 + -10
2x + -4y = 0 + -10

Combine like terms: 0 + -10 = -10
2x + -4y = -10

Add '4y' to each side of the equation.
2x + -4y + 4y = -10 + 4y

Combine like terms: -4y + 4y = 0
2x + 0 = -10 + 4y
2x = -10 + 4y

Divide each side by '2'.
x = -5 + 2y

Simplifying
x = -5 + 2y

See similar equations:

| 4=-s | | N+(n-3)=59 | | 7x+2x+7=20x-4 | | -4x+5-x=x-13 | | 4x+6=5x+15 | | 3-2x=133 | | 3-2x=130 | | 3(x-2)=(x-2)2 | | -4+5-x=x-13 | | 4y+3=2y-1 | | -15x^2+78x-15=0 | | (2y+1)2-(2y-1)2=16 | | 15x^2-78x-15=0 | | X(5)+y(3)=266 | | 3(x-1)+4=2(x+3)+1 | | 5(10-x)+20+6x=80 | | 3-2(x-1)=4-3(x+1) | | -8m^4-12m^3-1871m^2+636m-457=0 | | 6-3(x+1)=2+3(2x+3) | | 3(3x-2)=2(2x-5) | | -16m^4-24m^3-3742m^2+1272m-934=0 | | (4-x^2)dy-4ydx=0 | | f(t)=sin(2t)*cos(2t) | | 4(x-3)+5=9 | | 3x-3+4=6 | | 10-(50+x)=15 | | 4x+24+5x+10=6x+6+5x+20 | | 5(1-3x)=-35 | | -2(5-5x)=-40 | | 11(x+1)=99 | | 7x-1=10x-10 | | 50-2x=90-4x |

Equations solver categories